2018
DOI: 10.1063/1.5024303
|View full text |Cite
|
Sign up to set email alerts
|

Broadband high sound absorption from labyrinthine metasurfaces

Abstract: Metamaterials are artificial structures which exhibit fascinating properties unreachable by traditional materials. Here, we report on the design, fabrication, and characterization of acoustic metasurfaces consisting of dead-end channels coiled in a 2D plane. It is found that when the area of the channel’s cross section is about 1/10 of the area (4.3 cm × 4.3 cm) of the upper surface of the building block, the sound loss in channels approaches to a critical value, resulting in near-perfect absorption (A &gt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Anomalous phenomena such as beam-steering (Figure 4(a)) and conversion of propagating waves to evanescent surface waves (Figure 4(b)) were observed using a tapered labyrinthine acoustic metasurface [52,97]. Numerous studies have shown superior performance in space coiling acoustic metasurfaces for real-world applications, including simultaneous modulation of phase shifts and amplitudes of transmitted waves [98], manipulation of sound radiation patterns (Figure 4(c)) [93], one-way acoustic wave propagation (Figure 4(d)) [94], three-dimensional acoustic focusing (Figure 4(e)) [95], acoustic vortex generation (Figure 4(f)) [53], acoustic focusing with high transmission efficiency and ultra-broadband frequency range [99,100], broadband high sound absorption [104], and cloaking [105]. Space coiling structures provide a new way to manipulate acoustic waves by steering spatial phase shift gradients.…”
Section: Acoustic Metasurface With Space Coiling Structuresmentioning
confidence: 99%
“…Anomalous phenomena such as beam-steering (Figure 4(a)) and conversion of propagating waves to evanescent surface waves (Figure 4(b)) were observed using a tapered labyrinthine acoustic metasurface [52,97]. Numerous studies have shown superior performance in space coiling acoustic metasurfaces for real-world applications, including simultaneous modulation of phase shifts and amplitudes of transmitted waves [98], manipulation of sound radiation patterns (Figure 4(c)) [93], one-way acoustic wave propagation (Figure 4(d)) [94], three-dimensional acoustic focusing (Figure 4(e)) [95], acoustic vortex generation (Figure 4(f)) [53], acoustic focusing with high transmission efficiency and ultra-broadband frequency range [99,100], broadband high sound absorption [104], and cloaking [105]. Space coiling structures provide a new way to manipulate acoustic waves by steering spatial phase shift gradients.…”
Section: Acoustic Metasurface With Space Coiling Structuresmentioning
confidence: 99%
“…Sound reduction has always attracted a great deal of attention due to its practical applications in the fields of noise control, environmental protection and architectural acoustics. Recent development of acoustic metamaterials [1][2][3][4][5][6][7][8][9] and metasurfaces [10][11][12][13][14][15][16][17] provides alternative methods for designing various sound insulation and sound absorption systems based on different types of unit cells, such as Helmholtz resonators, [18][19][20][21][22][23][24] coiled Fabry-Perot resonators, [25][26][27] sound membranes, [28][29][30][31] metasurface-based structures, [32][33][34][35][36][37][38][39][40] and split-ring-resonators. [41,42] Generally, these systems have the advantages of high-performance sound insulation and absorption.…”
Section: Introductionmentioning
confidence: 99%
“…For more than one decade, the rapid expansion of acoustic metamaterials and metasurfaces has paved a way to manipulate the acoustic wave in unprecedented ways such as negative refraction 79 , subwavelength imaging 10,11 , cloaking 12,13 , and one-way transmission 14,15 . Metasurfaces are generally thin structures having subwavelength thickness consisting of unit cells that could give rise to numerous intriguing phenomena 16,17 . With an emphasis on their planarity and ultrathin thickness, metasurfaces are also claimed by some researchers as the planarized version of metamaterials, because both exhibit unusual properties 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…With an emphasis on their planarity and ultrathin thickness, metasurfaces are also claimed by some researchers as the planarized version of metamaterials, because both exhibit unusual properties 18,19 . One important category of acoustic metasurfaces is the absorptive metasurface 17,1945 , which exhibits super absorption for incident waves within a deep subwavelength thickness. Over the past few years, a host of absorptive metasurfaces have been proposed such as membrane-type resonators 2023 , coiled-up Helmholtz resonators and Fabry-Pérot channels 17,2432 , coherent perfect absorbers 33,34 and metaporous materials 3537 .…”
Section: Introductionmentioning
confidence: 99%